The heterogeneous expression patterns of serum tumor markers in non-small cell lung cancer patients are predictive factors for progression-free survival - Siqi Li; Zihang Zeng; Zixi Hong; Jiali Li; Conghua Xie (Discover Oncology)
Abstract Purpose Non-small cell lung cancer (NSCLC) patients may exhibit tumor marker expression patterns that do not align with their pathological subtype, yet the clinical significance of these mismatches remains unclear. This study aims to identify novel tumor marker expression patterns and explore their relationship with tumor heterogeneity and progression-free survival (PFS) in NSCLC patients. Methods Clinical data and serum tumor marker values were collected from 142 patients with stage III–V, unresectable NSCLC in the Zhongnan Hospital of Wuhan University. The Self-organizing map algorithm was used to generate novel tumor marker patterns. We analyzed the association of these patterns with clinicopathological features and prognosis. The in vitro experiment was conducted to evaluate the impact of CA125 on the malignant behavior of squamous cell carcinoma cell lines. Results We identified a pattern of low expression of SCC and high expression of CA125 in squamous cell carcinoma patients (HR 2.1704, P = 0.0304), as well as low expression of CEA and high expression of SCC in adenocarcinoma patients (HR 2.3771, P = 0.0235). Both patterns were significant predictors of poor prognosis. Furthermore, squamous cell carcinoma cell lines cultured in a high-CA125 environment exhibited accelerated proliferation in vitro. Conclusion NSCLC patients with a pattern of tumor markers mismatched to their pathological type had unfavourable PFS, suggesting a potentially higher degree of tumor heterogeneity.